2020
DOI: 10.3390/ijerph17186441
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of Electrocardiographic T Wave Parameters Recorded during the Head-Up Tilt Table Test as Independent Markers of Syncope Severity in Children

Abstract: The head-up tilt table test (HUTT) with the upright phase is used to help determine an imbalance of the sympathetic nervous system that is related to abnormal electrocardiographic repolarization in children with vasovagal syncope (VVS) and also in patients with the long QT syndrome (LQTS). The study attempted to evaluate T wave morphology and QT and TpTe (Tpeak–Tend) intervals recorded in ECG during the HUTT for a more accurate diagnosis of children with VVS. The group investigated 70 children with a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In a study by Markiewicz-Łoskot and colleagues, they found that patients who experienced vasovagal syncope had longer T wave parameters [12]. Our explanation for this phenomenon is possible muscarinic receptor stimulation of some potassium channels which are responsible for the duration of action potential.…”
Section: Discussionmentioning
confidence: 72%
“…In a study by Markiewicz-Łoskot and colleagues, they found that patients who experienced vasovagal syncope had longer T wave parameters [12]. Our explanation for this phenomenon is possible muscarinic receptor stimulation of some potassium channels which are responsible for the duration of action potential.…”
Section: Discussionmentioning
confidence: 72%
“…In a very recent study by Loskot et al, 29 QT intervals were similar between NMS and control groups both at baseline and in the recovery phase, but T peak to T end interval, which is a newly suggested indicator of repolarization disparity, has been significantly higher in syncopal group compared to control group.…”
Section: Discussionmentioning
confidence: 84%
“…As a more sensitive indicator for judging arrhythmia, it can eliminate the influence of heart rate and individual QT interval variability on Tp-Te (54). Markiewicz-Łoskot et al (47) found that the Tp-Te interval in lead V5 was consistently prolonged during HUTT in 40 children with VVS compared to healthy children [in supine position: 89 ms vs. 80 ms, P < 0.01; syncope occurred: 100 ms vs. 60 ms, P < 0.01; after syncope: 90 ms vs. 80 ms, P < 0.01]. According to ROC, Tp-Te interval > 70 ms (AUC = 1) was recommended for predicted VVS with good sensitivity and specificity (both 100%).…”
Section: T Wave Amplitude and Morphologymentioning
confidence: 99%